2007
DOI: 10.3892/or.18.2.383
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of survivin expression and elevation of caspase-3 activity involved in pitavastatin-induced HepG 2 cell apoptosis

Abstract: Abstract. The aim of the present study was to research the apoptosis of human hepatocellular carcinoma cell line HepG 2 induced by pitavastatin. HepG 2 cells were treated with increasing doses of pitavastatin or with mevalonic acid for 48 h. The proliferation of cells was detected with WST-8. The morphology of the nucleus was observed under a microscope by Hoechst 33258 staining. The apoptosis peaks were examined by flow cytometry. The expression of survivin mRNA was examined with RT-PCR. The caspase-3 activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
1
8
1
Order By: Relevance
“…Previous studies only described survivin down-regulation itself by statin [18,19]. Our result demonstrates more specific and detailed mechanism than the prior reports.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Previous studies only described survivin down-regulation itself by statin [18,19]. Our result demonstrates more specific and detailed mechanism than the prior reports.…”
Section: Discussioncontrasting
confidence: 58%
“…Recently, considerable evidence has suggested that statininduced apoptosis is associated with down-regulation of survivin expression in cancer cells [19]. However, the mechanism underlying deregulated survivin by simvastatin on human non-small cell lung cancer cells has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous data have revealed that survivin is one of the genes most consistently over-expressed in tumor cells and plays important roles in both cell proliferation and cell death (30). Downregulation of survivin expression may lead to programmed cell death (31), indicating that it may be an appealing new target for novel therapy in cancer (32). Our results show that tanshinone IIA may trigger apoptosis in COC1/DDP cells by downregulating survivin levels via activation of p38 MAPK.…”
Section: Discussionmentioning
confidence: 53%
“…Apoptosis plays a key role in the pathogenesis of cancers and the genes relating to this process are focus of interest in the studies of cancer onset and progression. It is well-known that Bax and BCL-2 are transcriptional targets for the tumor suppression protein p53 (17), which is responsible for the induction of cell cycle arrest and/or apoptosis in response to DNA damage (21). …”
Section: Discussionmentioning
confidence: 99%